Building a virtual union catalogue for Arabic journal articles in Malaysian libraries using open source solutions - Solihu, Abdul Kabir Hussain; Mansor, Yushiana; Awang Abu Bakar, Normi Sham; Md Ghalib, Mohd. Feham; Al Haek, Mohammed (2014)
A considerable number of Malaysian libraries are housing Arabic collections to support the needs of their users. Currently, there is no bibliographical database of scholarly articles published in Arabic periodicals available in Malaysian libraries. To know what is published in Arabic periodicals a researcher has to check these voluminous journals manually from one library to another. This has created great difficulties for researchers and consequently impaired the quality of their publications in Arabic The aim of this paper is to discuss the ongoing research project at the International Islamic University Malaysia (IIUM) to create a virtual union catalogue for collections of Arabic journal articles. The project, tagged “My Index Arabicus” (Malaysian Index Arabicus), was designed to develop a single search platform to retrieve the bibliographic records of Arabic articles indexed from selected Arabic journals available in five Malaysian university libraries. Using DSpace open source digital library software with the Dublin Core metadata standard, the collected materials are synchronized into a single database searchable by different access points, and accessible online to all users of Malaysian academic libraries. A total of 1,000 records are currently hosted in the system. It is estimated that the system will host more than 10,000 records by the end of the project. Experience from the project has shed light on technical knowledge and skills in computing, cataloguing of Arabic articles, and institutional infrastructure.